Economic opportunities of AMI implementation : a review (2019)
Advanced Metering Infrastructure (AMI) is rapidly becoming a key element for the modernization and disruption of power grids, generating benefits and opportunities to all actors involved in its implementation. In order to guarantee a correct deployment of AMI, a wide knowledge of its advantages and challenges is needed, that takes into account previous experiences and latest advances that have been made in the field. In this paper, a review of literature is used as a mean to collect the relevant information concerning AMI, so as to conclude which are the opportunities that AMI provides to all parties involved. This is achieved by searching in the most important data bases and specialized sources such as IEEE and IEA. It was found that this infrastructure, does indeed help improve efficiency and leads to positive economic effects impacting variables like costs and prices.